New Physical Scaling Approach to compensate the part contraction in drawing operations. Issue 1 (November 2020) - Birkert, A; Zimmermann, P; Hartmann, B; Scholle, M; Straub, M
Abstract: Further increasing requirements to the quality of car body components represent a huge challenge for the process planner. Springback effects are causing dimensional deviations of the car body components from their respective target geometry. Both elastic membrane and bending stresses result in global and regional distortions and deflections. In addition to these effects in particular the membrane stresses furthermore result in a contraction of the drawshell with the effect that the drawshell is smaller than the tool after drawing. In order to compensate this contraction the drawing tool has to be increased. This process is known as the so-called scaling. An appropriate scaling should result in a contracted part which has the same surface area and unwound lengths as the target geometry. In case of deviations of the unwound lengths unwanted plastic deformations of the part in subsequent operations have to be expected and the part's assembly dimensions will differ from the target geometry which can cause significant quality issues in the car body. Today the scaling is usually done by increasing the tool with a unique global scaling factor or with different scaling factors for different directions. However, since the contraction varies along the part surface in reality the results are only suboptimal. Here a new scaling approach is being presented which uses the simulation results to scale the tool surfaces locally. By doing so the locally different contractions can be better compensated.